Asociación de polimorfismos genéticos de las razas Cebú y Romosinuano con el desarrollo muscular y peso vivo final (2011)
A study was undertaken in the municipality of Monter´ıa (Cordoba, Colombia) in order to determine the eﬀect that has the single nucleotide polymorphism of MYF5 gene of BTA5 on live weight at slaughter of a population of 57 animals of Zebu Brahman and Romosinuano. Through this test it was found that the homozygous variant allele 11 was not segregated in the population being homozygous alleles identiﬁed only 22 and the respective heterozygotes 12. Because the average live weight at which animals reach slaughter in Colombia is 430Kg, this group was divided into above and below from that average. The data were analyzed using a logistic regression model for binomial data. The results showed that the best performing allele was homozygous in Romosinuano, followed by the same allele in Zebu, which shows that there is a direct association of the homozygous polymorphism with a better response on the ﬁnal live weight of slaughter animals. On the other hand, it was observed that the two variables have an eﬀect on slaughter weight.